1974
DOI: 10.1128/jvi.13.3.690-698.1974
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression During the Development of Bacteriophage φ29 III. Analysis of Viral-Specific Protein Synthesis with Suppressible Mutants

Abstract: Fifty-four suppressible mutants of bacteriophage 429 have been isolated with a variety of mutagens and assigned to eight complementation groups. Viralspecific protein synthesis in UV light-irradiated, nonsuppressing Bacillus subtilis 60084 was analyzed with exponential acrylamide gels. Four additional 029 10"1 PFU of 029+ in TM buffer (0.01 M Tris-0.01 M MgSO4, pH 7.4). The mixture was incubated at room temperature (24 C) with gentle stirring. Samples (0.05 ml) were removed at 10-min intervals, and the reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

1978
1978
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 12 publications
(24 reference statements)
5
35
0
Order By: Relevance
“…More recently, Salas et al (37) have shown that the major tryptic peptides of the terminal protein are very similar to those of the @029 gene 3 protein. It is known that gene 3 is involved in DNA replication of 4)29 (11,29,39,42) and that normal gene 3 protein is required continuously for replication of this viral DNA (28,42,44). Thus, these studies suggest that the terminal proteins are directly involved in DNA replication.…”
Section: Ito Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…More recently, Salas et al (37) have shown that the major tryptic peptides of the terminal protein are very similar to those of the @029 gene 3 protein. It is known that gene 3 is involved in DNA replication of 4)29 (11,29,39,42) and that normal gene 3 protein is required continuously for replication of this viral DNA (28,42,44). Thus, these studies suggest that the terminal proteins are directly involved in DNA replication.…”
Section: Ito Discussionmentioning
confidence: 92%
“…Furthermore, Salas and colleagues have shown that tryptic peptides of the DNA-bound protein are very similar, if not identical, to those of the 429 gene 3 protein (37). The gene 3 protein has been shown to be essential for 429 DNA replication (11,28,29,42). In this paper, further evidence is presented that the protein is linked covalently to the 5' ternini of the 429 DNA.…”
mentioning
confidence: 73%
“…It was not possible to detect TP in cells at the very early stages of infection, presumably due to the very low levels of TP in cells prior to the amplification of DNA during the replication cycle. However, during the middle stage of infection, after the onset of φ29 DNA replication (see below; Ivarie and Pène, 1973; McGuire et al ., 1974), a punctate fluorescent signal was observed that appeared to localize around the host cell chromosome (Figure 3D and F). By the late infection stage, the TP‐specific signals appeared to fill the volume occupied by the DNA (Figure 3G and I).…”
Section: Resultsmentioning
confidence: 99%
“…We wished to determine whether phage φ29 DNA replication was associated with these host cell replication factories, as they could be sites where nucleotide precursors are particularly concentrated, or if it occurred in a completely separate region(s) of the cell. Evidence has been obtained that phage φ29 DNA replication is associated with the cell membrane (Ivarie and Pène, 1973; McGuire et al ., 1974, 1977; Bravo and Salas, 1997, 1998; W.J.J.Meijer, A.Serna‐Rico and M.Salas, submitted), as is host cell DNA replication.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a correlation between the formation of such complexes and synthesis of viral DNA was reported. For example, parental /29 DNA encoding a thermosensitive DNA polymerase was not membrane-associated at the restrictive temperature, unless cells were co-infected with wild-type phage [178][179][180]. Based on these findings, it was postulated that in vivo /29 DNA replication takes place associated to the bacterial membrane.…”
Section: Protein P1mentioning
confidence: 99%